2011
DOI: 10.1016/j.bbadis.2011.01.009
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAcylation is a novel regulator of lung and colon cancer malignancy

Abstract: O-GlcNAc is a monosaccharide attached to serine or threonine hydroxyl moieties on numerous nuclear and cytoplasmic proteins; O-GlcNAcylation is dynamically regulated by O-GlcNAc transferase (OGT) and O-GlcNAcase (OGA). Although recent studies have shown that O-GlcNAcylation plays essential roles in breast cancer progression, it is also necessary to know whether O-GlcNAcylation is involved in other types of human cancer. In this study, O-GlcNAcylation levels and the expressions of OGT and OGA in human lung and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
193
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 215 publications
(217 citation statements)
references
References 29 publications
21
193
0
3
Order By: Relevance
“…1). These findings are in accordance with previous reports describing enhanced O-GlcNAcylation in breast cancer metastatic lymph nodes compared with their primary tumor tissues and increased levels of O-GlcNAcylation and OGT in lung and colon tumor tissues compared with adjacent tissues (10,11). Increased O-GlcNAcylation and elevated OGT expression were also found in several breast cancer cell lines (7).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…1). These findings are in accordance with previous reports describing enhanced O-GlcNAcylation in breast cancer metastatic lymph nodes compared with their primary tumor tissues and increased levels of O-GlcNAcylation and OGT in lung and colon tumor tissues compared with adjacent tissues (10,11). Increased O-GlcNAcylation and elevated OGT expression were also found in several breast cancer cell lines (7).…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, enhanced growth of the SW620 clone compared with the SW480 clone in both culture and agar was previously shown (29,30). These data suggest that O-GlcNAcylation enhances anchorage-independent growth, an assumption supported by a previous report showing that colony formation by lung and colon cancer cells was reduced by OGT silencing and increased by OGA inhibition (10). Similarly, OGT silencing in breast cancer cells inhibited tumor growth in vitro and in vivo and decreased cell cycle progression (7).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…As a glycolytic pathway, HBP can enhance the level of UDP-GlcNAc, and thus, the activity of OGT, which may lead to an increase in the global O-GlcNAc level (summed over all proteins) in cancer cells. We have previously demonstrated that the global O-GlcNAc level is increased in breast, lung and colon cancer tissues as compared to respective adjacent tissues (11,12). In addition, other research groups have shown that O-GlcNAcylation is increased in breast, prostate and pancreatic cancer cell lines (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%